Intersections of Open Educational Resources and Information Literacy - Cullen, Mary Ann; Dill, Elizabeth (Open textbook library., 2022)
"The present volume is timely not only because it models creative and effective strategies to advance both open education and information literacy, but especially because it poses critical questions and urges practitioners to go well beyond questions of access to and the use of information. It demands reflection on what is being accessed (and what is not), who is gaining access (and who is not), who is providing access (and who is not), and what the goal is of this access (and what lies beyond access)."—from the Foreword by Rajiv S. Jhangiani Information literacy skills are key when finding, using, adapting, and producing open educational resources (OER). Educators who wish to include OER for their students need to be able to find these resources and use them according to their permissions. When open pedagogical methods are employed, students need to be able to use information literacy skills as they compile, reuse, and create open resources. Intersections of Open Educational Resources and Information Literacy captures current open education and information literacy theory and practice and provides inspiration for the future. Chapters include practical applications, theoretical musings, literature reviews, and case studies and discuss social justice issues, collaboration, open pedagogy, training, and advocacy. The book is divided into six parts: Foundations Teaching Info Lit with OER Librarian Support of Open Pedagogy/OER Social Justice/Untold Stories Student Advocacy Spreading the Love: Training Future Advocates and Practitioners Chapters cover topics including library-led OER creation; digital cultural heritage and the intersections of primary source literacy and information literacy; situated learning and open pedagogy; critical librarianship and open education; and developing student OER leaders. Intersections of Open Educational Resources and Information Literacy—which went through an open peer review process—informs and inspires on OER, info lit, and their many iterative convergences. It is available as an open access edition at https://bit.ly/ACRLOERInfoLit.